Toxic Effect Of Glyphosate-Based Herbicide On Antioxidant Defense System And Heat Shock Protein 70 Expression In Monopterus Cuchia (Hamilton) (Applied Biological Research, 2018)
The present study was aimed to evaluate the toxicological effect on antioxidant  defense system in Monopterus cuchia induced by commercial formulation of  Glyphosate EXCEL MERA 71. In the study, fish were exposed to sub-lethal  concentrations of 1 and 2 mg L-1. LC50 value for glyphosate at 96 h exposure  could not be determined because no fish mortality was observed even at the  maximum concentration tested 200 mg L-1. After 6, 24, 96 and 168 h of  exposure, there were significant decrease in the level of red blood cells,  haemoglobin concentration and a significant increase in white blood cells  count in both treated groups. The enzyme alanine aminotransferase decreased  whereas aspartate aminotransferase and alkaline phosphatase showed  increase in comparisonto control which were analyzed in serum. The fish  showed transient decrease in superoxide dismutase and catalase activities and  the non-enzymatic antioxidant reduced glutathione showed repressed activity  after glyphosate exposure. However, glutathione-S-transferase activity significantly increased in kidney and intestine and decreased in liver in treated  groups. Moreover, the present study also investigated the possible stimulation  of heat shock protein 70 (Hsp70) mRNA and glyphosate exposure led to a  significant increase in the levels of mRNA transcript in liver and kidney.
Keywords: Antioxidant; glyphosate; Hsp70; hematology